Self-DNA inhibitory effects: Underlying mechanisms and ecological implications. (2nd April 2016) - Cartenì, Fabrizio; Bonanomi, Giuliano; Giannino, Francesco; Incerti, Guido; Vincenot, Christian Ernest; Chiusano, Maria Luisa; Mazzoleni, Stefano
ABSTRACT: DNA is usually known as the molecule that carries the instructions necessary for cell functioning and genetic inheritance. A recent discovery reported a new functional role for extracellular DNA. After fragmentation, either by natural or artificial decomposition, small DNA molecules (between ∼50 and ∼2000 bp) exert a species specific inhibitory effect on individuals of the same species. Evidence shows that such effect occurs for a wide range of organisms, suggesting a general biological process. In this paper we explore the possible molecular mechanisms behind those findings and discuss the ecological implications, specifically those related to plant species coexistence.